Acute lung injury: apoptosis in effector and target cells of the upper and lower airway compartment - Z'graggen, B Roth (Blackwell Science Inc, 2010)
Apoptotic cell death has been considered an underlying mechanism in acute lung injury. To evaluate the evidence of this process, apoptosis rate was determined in effector cells (alveolar macrophages, neutrophils) and target cells (tracheobronchial and alveolar epithelial cells) of the respiratory compartment upon exposure to hypoxia and endotoxin stimulation in vitro. Cells were exposed to 5% oxygen or incubated with lipopolysaccharide (LPS) for 4, 8 and 24 h, and activity of caspase-3, -8 and -9 was determined. Caspase-3 of alveolar macrophages was increased at all three time-points upon LPS stimulation, while hypoxia did not affect apoptosis rate at early time-points. In neutrophils, apoptosis was decreased in an early phase of hypoxia at 4 h. However, enhanced expression of caspase-3 activity was seen at 8 and 24 h. In the presence of LPS a decreased apoptosis rate was observed at 8 h compared to controls, while it was increased at 24 h. Tracheobronchial as well as alveolar epithelial cells experienced an enhanced caspase-3 activity upon LPS stimulation with no change of apoptosis rate under hypoxia. While increased apoptosis rate is triggered through an intrinsic and extrinsic pathway in alveolar macrophages, intrinsic signalling is activated in tracheobronchial epithelial cells. The exact pathway pattern in neutrophils and alveolar epithelial cells could not be determined. These data clearly demonstrate that upon injury each cell type experiences its own apoptosis pattern. Further experiments need to be performed to determine the functional role of these apoptotic processes in acute lung injury.